2001
DOI: 10.1114/1.1359449
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic Model of Acute Platelet Accumulation in Thrombogenic Stenoses

Abstract: Thrombosis on an atherosclerotic lesion can cause heart attack or stroke. Thrombosis may be triggered by plaque rupture or erosion, creating a thrombogenic stenosis. To measure and model this situation, collagen-coated stenoses have been exposed to nonanticoagulated blood in a baboon ex vivo shunt. The maximum rate of platelet accumulation, measured using a gamma camera, was highest in the throat region of moderate and severe stenoses, and increased with increasing stenosis severity. A species transport model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 35 publications
3
76
0
Order By: Relevance
“…Fluid dynamic studies from the 1990s reported that stenotic regions influenced platelet aggregation by way of flow perturbations and recirculation zones (19,20). In particular, collagen ligands in combination with extremely high shear rates were used to detect poststenotic aggregate formation (21,22). However, in the present study, the flow conditions in the microfluidics channel were flow in straight channels.…”
Section: Discussionmentioning
confidence: 78%
“…Fluid dynamic studies from the 1990s reported that stenotic regions influenced platelet aggregation by way of flow perturbations and recirculation zones (19,20). In particular, collagen ligands in combination with extremely high shear rates were used to detect poststenotic aggregate formation (21,22). However, in the present study, the flow conditions in the microfluidics channel were flow in straight channels.…”
Section: Discussionmentioning
confidence: 78%
“…In experiments with ␥ w ranging from a value found in normal arterioles (2000 s Ϫ1 ) to a value found at points of lumen restriction in atherosclerotic coronary arteries (40 000 s Ϫ1 ), 14,26,27 we observed that a single DAP positioned either within the platelet body or at the upstream end of a tether could be the only membrane area anchored to the surface. In the former cases it acted as a pivot during rotational or flip movements ( Figure 1E; Movie S5); in the latter, it held the whole platelet body stationary ( Figure 1F; Movie S6).…”
Section: Platelet-derived Tethers and Microparticles In Flow Form Thrmentioning
confidence: 73%
“…Above this range, blood can be considered Newtonian. The aggregability of RBCs, in turn, is dependent on the concentration of plasma proteins, especially large molecules like fibrinogen and Dextran, the hematocrit, as well as the size, shape, and rigidity of RBCs [6,7,27]. The functional dependence of deformability includes the rigidity of the RBC as well as the hematocrit-since greater packing requires more net energy to deform the cells.…”
Section: Krieger Exponent and Shear Thinningmentioning
confidence: 99%
“…The latter property is important for simulating rheological anomalies that may occur in disease. The former property is important to account for the effect of hemodilution or hemo-concentration, as well as the non-uniform distribution of red blood cells in several situations, such as capillary tubes [1], plasma skimming [2], bifurcations [3], rotary blood pumps [4], and sudden expansions [5][6][7]. Several of the models presented in Tables 1 and 2 exhibit mathematical discontinuities with respect to shear rate and/or hematocrit.…”
Section: Introductionmentioning
confidence: 99%